The territorial nature and power of human capital in urban development processes from the perspective of the path dependence concept - Przygodzki, Zbigniew; Adamus, Jagoda (Quaestiones Geographicae, 2024)
Knowledge and human capital are gaining importance as determinants of urban and regional development on a global scale. We can observe a simultaneous increase in the mobility of human capital, the availability of knowledge, and an increase in the importance of location. This phenomenon is sometimes referred to as glocalisation. Mobile and highly valuable human capital are being territorialised. From the city’s point of view, is this an opportunity or a threat? The question can be asked whether the territorialisation of human capital has an impact on the durability of urban development. It is not obvious whether it helps to develop competitive potential and competitive advantages of an area only temporarily or in the long term. An analysis using elements of the path dependency theory can provide answers to these questions. It considers both the complexity of the research subject and the evolutionary nature of development processes. Therefore, the fundamental question of this article is whether the territorialisation of human capital affects the durability of urban development. The main findings of the study show that both the size of a city and the rate of demographic growth affect the choice of the type of development path. Cities with high demographic growth rates and complex development strategies enter reactive paths. This type of path guarantees the durability of development processes.